Transcription by an immobilized RNA polymerase from bacteriophage T7 and the topology of transcription. - Cook, P; Gove, F (1992)
It is often assumed that a polymerase moves along the template as it synthesizes RNA. However, a polymerase that tracks along a helical strand will generate a transcript that is entwined about the template. No such interlocking results if the polymerase is immobile and the template moves past it. Therefore we investigated whether immobilization inhibits the RNA polymerase of T7 bacteriophage using a hybrid protein, in which the polymerase is connected through a peptide linker to an immobilizing domain, which in turn was attached through an antibody to protein A covalently linked to plastic beads. Polymerase could be released by cleaving the linker with a protease, factor Xa. Comparison of the activity of the bound and free enzymes showed that immobilization reduced the rate of initiation about fivefold. However, when re-initiation was eliminated by removing excess template, immobilization was found to have little effect on the rate of elongation. Perhaps the untwining problem is sidestepped in vivo by immobilizing the polymerase.